The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1978
DOI: 10.1111/j.1528-1157.1978.tb04500.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Epilepsy in Children: A Follow‐up Study Three Years After the First Seizure

Abstract: Summary A prospective epidemiological study of the incidence of epilepsy was performed in a Swedish county. The population studied during the incidence period consisted of 52,252 children âged 0–15 years. Seventy‐four children who had had their first seizure during the period February 1, 1973‐January 31, 1974 were reexamined 3 years later. Forty‐three children were classified as having epilepsy at the follow‐up, which gives an incidence of 82/100,000. The most frequent types of epilepsy found were: primary gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
71
3
5

Year Published

1996
1996
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(88 citation statements)
references
References 9 publications
9
71
3
5
Order By: Relevance
“…Epileptiform activity in form of spike/sharp waves was present in 68% of the patients. As seen in table-11, the percentage of epileptiform activity in the studies by Waaler [13] , Blom [32] were higher than our study. However, Waaler et.…”
contrasting
confidence: 52%
“…Epileptiform activity in form of spike/sharp waves was present in 68% of the patients. As seen in table-11, the percentage of epileptiform activity in the studies by Waaler [13] , Blom [32] were higher than our study. However, Waaler et.…”
contrasting
confidence: 52%
“…In their study of 43 patients, Blom et al (34) reported that 81 % of patients had an epileptiform EEG pattern in their initial recordings, whereas this figure had decreased to 62% at the follow-up examination 3 years later. Tsuboi (41) found that 58.5% of 378 children with epilepsy aged 6-14 years, had paroxysmal EEG activity by their first examination.…”
Section: Discussionmentioning
confidence: 96%
“…Assim, os casos que tiveram recorrência muito precoce não foram computados para nosso estudo, pois a partir da segunda crise foram diagnosticados como epilépticos. Na literatura, os riscos de recorrência em crianças, após uma única crise, variam de 27% a 61% 2,6,7,[10][11][12][13][14][15][16] . Estudos que selecionam crianças no momento da crise, e excluem aquelas com crises anteriores, demonstram riscos de 34% a 44% 2,6,7,9 .Trabalhos que recrutam indivíduos tardia ou retrospectivamente, de laboratórios de EEG, mas excluem crises anteriores, mostram riscos levemente maiores como 48% a 52% 11,14 .…”
Section: Fig 3 Curva De Sobrevivência Ajustada Para O Conjunto Globaunclassified
“…Estudos que selecionam crianças no momento da crise, e excluem aquelas com crises anteriores, demonstram riscos de 34% a 44% 2,6,7,9 .Trabalhos que recrutam indivíduos tardia ou retrospectivamente, de laboratórios de EEG, mas excluem crises anteriores, mostram riscos levemente maiores como 48% a 52% 11,14 . Pesquisas incluindo crianças que já haviam apresentado crises referem riscos altos de recorrência, 61% a 62% 10,16 . Finalmente, estudos que distinguem a etiologia das crises mostram dados de recorrência distintos para os dois grupos: G-CI -37% e 29% no quinto ano 7,9 ; G -CSR -66% e 48% no quinto ano 7,9 Em nossa população, também de idade inferior a 19 anos, o risco de recorrência foi avaliado em: 18% no primeiro semestre, 27% no primeiro ano, 35% no segundo ano e 38% no terceiro ano (Fig 3).…”
Section: Fig 3 Curva De Sobrevivência Ajustada Para O Conjunto Globaunclassified